O medo de cair e o histórico de quedas influenciam na cinemática de tarefas funcionais em idosos - Júlio, Cíntia Elord (2022)
Background: Changes in the aging process such as lower muscle strength, poorer motor coordination and balance favor the occurrence of falls in the elderly population. Most of the time, these falls occur during some activity of daily living. In addition, the fear of falling is an important factor that can favor the occurrence of falls. Several tasks related to the risk of falling present kinematic changes in the elderly population and the factors behind these changes seem to go beyond the history of falls, since non-fallers with fear of falling also present kinematic changes in gait. Objective study 1: To verify if the kinematics of some functional tasks differentiate fallers from non-fallers and which one differentiates more. Objective Study 2: To verify how the kinematics of functional tasks behaves in the elderly under the influence of the history of falls and fear of falling. Methods: Cross-sectional observational study approved by the ethics committee evaluated 68 elderly people aged 60 years or older. The elderly were divided into 2 groups in study 1 (with and without a history of falls, 34 in each group) and in study 2 into 4 groups (non-fallers with low fear of falling, non-fallers with high fear of falling, fallers with low fear of falling and fallers with high fear of falling, 17 in each group). Clinical and sociodemographic data were collected. Assessment instruments were used for quality of life, level of physical activity, frailty, fear of falling, risk of falls and history of falls. Finally, the kinematic evaluation of the tasks was performed. The three-dimensional kinematics data were analyzed using the MDP and to identify which task and group presented the greatest difference, the Z-score of the average of the MDP was calculated. To compare the sample characterization variables, Student's t test (parametric), the Mann-Whitney test (non-parametric) and the Chi-square test (nominal) were performed. The sample description variables and the time to perform each task were tested by analysis of variance (MANOVA), with Bonferroni post - hoc to identify differences between groups. The significance level was defined as 5% (p<0.05). Results: All tasks showed significant differences between groups in study 1 and 2. To compare the MDP results, ANOVA showed interaction between groups (= 0.67, F= 5.085, p<0.0001) in study 1 and (= 0.30 F= 4,870 p<0.0001) in study 2. Conclusion: Although all the tasks differentiated fallers from non-fallers, the task that most differentiated was the descent of stairs. The fear of falling and the history of falls influence the kinematics of different functional tasks and when the history of falls was added to the high fear, the differences were even greater when compared to the control group.